Engineering microbiomes for enhanced bioremediation. - Xihui Xu; Jiandong Jiang (PLoS Biology)
Bioremediation using synthetic microbiomes offers significant advantages over traditional single-strain-based approaches. In this Perspective, we outline 5 important considerations for the rational design of pollutant-degrading microbiomes for enhanced bioremediation.